Status of the Reactive Extraction as a Method of Separation. (19th March 2015) - Datta, Dipaloy; Kumar, Sushil; Uslu, Hasan
Abstract : The prospective function of a novel energy efficient fermentation technology has been getting great attention in the past fifty years due to the quick raise in petroleum costs. Fermentation chemicals are still limited in the modern market in huge part because of trouble in recovery of carboxylic acids. Therefore, it is needed considerable development in the current recovery technology. Carboxylic acids have been used as the majority of fermentation chemicals. This paper presents a state-of-the-art review on the reactive extraction of carboxylic acids from fermentation broths. This paper principally focuses on reactive extraction that is found to be a capable option to the proper recovery methods.